2002
DOI: 10.1080/15216540214316
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitochondrial Gene Expression by Retinoids

Abstract: SummarySeveral nuclear hormone receptors have been localized to the mitochondrial compartment. Evidence supports the hypothesis that these receptors directly regulate mitochondrial transcription. Retinoic acid has also been shown to regulate mitochondrial transcription and function. This review discusses mechanisms of mitochondrial transcription and how retinoic acid may either indirectly or directly regulate mitochondrial transcription. How retinoic acid may affect individual nutrient requirements is also dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The ND5 gene expression is the only mitochondrial protein-coding gene that is tightly regulated, and the rate of ND5 synthesis appears to control the overall rate of respiration (Bai et al 2000; Chomyn 2001). Interestingly, this regulation appears due to differential ND5 mRNA stabilization, and mRNA levels have been reported to be upregulated by nutrients or cholera pathogenesis, and downregulated during hypoxia (Everts and Berdanier 2002; Piruat and Lopez-Barneo 2005; Sarkar et al 2005). The ND6 mRNA is the only protein-coding mRNA generated from the L-strand specific primary transcript.…”
Section: Discussionmentioning
confidence: 99%
“…The ND5 gene expression is the only mitochondrial protein-coding gene that is tightly regulated, and the rate of ND5 synthesis appears to control the overall rate of respiration (Bai et al 2000; Chomyn 2001). Interestingly, this regulation appears due to differential ND5 mRNA stabilization, and mRNA levels have been reported to be upregulated by nutrients or cholera pathogenesis, and downregulated during hypoxia (Everts and Berdanier 2002; Piruat and Lopez-Barneo 2005; Sarkar et al 2005). The ND6 mRNA is the only protein-coding mRNA generated from the L-strand specific primary transcript.…”
Section: Discussionmentioning
confidence: 99%
“…To date, coordination between the nuclear and mitochondrial genomes has been achieved only by two elements: the mitochondrial transcription factor A (Tfam) and PGC-1 (40). In an effort to elucidate this molecular circuitry several groups examined the mitochondrion failure-related gene expression differences using commercially-available microarrays.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al observed increased levels of expression of ND1, ND6 and COX I genes after treating cells with 9-cis RA. Putative retinoic acid response elements (RARE) have been found in the D-loop region of the mtDNA, suggesting direct mitochondrial transcription regulation by RA (Everts and Berdanier 2002).…”
Section: Transcription Regulation At the H2 Terminationmentioning
confidence: 99%